The Psychological and Academic Effects of Studying From the Home and Host Country During the COVID-19 Pandemic - Wilczewski, Michał; Gorbaniuk, Oleg; Giuri, Paola (Frontiers in Psychology, 2021)
Objective: This study explored the psychological and academic effects of studying online from the home vis-à-vis host country during the COVID-19 pandemic in the experience of international students at the University of Warsaw, Poland. Methods: A total of 357 international students from 62 countries (236 in the host country and 121 in the home country) completed an online questionnaire survey two months after transition to online learning. We studied students’ levels of loneliness, life and academic satisfaction, acculturative stress, academic adjustment, performance, loyalty, and perceptions of the online learning experience. Results: The country-of-residence variable had no statistically significant effects on most psychological and academic variables. Significant effects were observed only for two academic variables. Specifically, students who returned to the home country found online communication with other students more contributing to their online learning experience and exhibited higher academic adjustment than students who remained in the host country. This suggests the positive influence of (peer and familial) support on online learning experience from the home country. Furthermore, a significant difference in experiencing acculturative stress occurred for students in quarantine/self-isolation in the host country, which expands prior literature on the disruptive effects of social distancing on students’ mental health. Finally, this study confirmed the expected increased levels of loneliness among self-isolating students in both countries, hence extending prior results to the home- and host-country contexts. No relationship between self-isolation and students’ life or academic satisfaction was found, which is explained by the specific nature of the learning-from-home experience.